(untitled) (AYUSHDHARA, 2017)
Pandu Roga was well known to Indian people science since Vedic Period. It is described in full length by all the Acharyas of Ayurveda as a specific disease with its own Pathogenesis and treatment. In Panduroga change the color of the body like pallor of skin, sclera, nail, tongue etc. due to Rakta-alpata means Hemoglobin level decrease than the normal level. It is related with both important Dhatu Rasa and Rakta. We can correlate this disease to Anaemia in modern science. Anaemia is the world’s second leading cause of disability and is responsible for about 1 million deaths a year. It is therefore important for Ayurvedic scholar to search scientific reason behind the disease. With this research interest the present study has been undertaken thoroughly review of Panduroga. Three general principles of treatment have been mentioned in Charaka Samhita. They are Daivavyapashraya, Yuktivyapashraya and Satvawajya. Here only Yuktivyapashraya Chikitsa has been mentioned. Single drugs which have been used in Pandu are - Lauha Bhasma, Mandura Bhasma, Pure Kaseesa, Shilajita, Vardhamana Pippali etc. Compound drugs which are of vegetable origin e.g. Triphala, Phalatrikadi Kwatha, Punarnavashtaka Kwatha, Vidangavaleha etc. Here also made some efforts to discuss every aspect of Panduroga in Ayurvedic point of view.